Risks of Teacher’s Professional Health - Dziuba, Tetiana (Psychological Prospects Journal, 2015)
The article reviews the results of an empirical study of professional health risks for the teacher. It was noted that the teacher’s negative emotions affect the emotional state of students directly and indirectly, inhibit the development of student’s creativity, cause irreversible deformation to the growing personality. It reviews the technique, which makes it possible to investigate the main factors of adverse effect on the teacher’s professional health for the following parameters: organization of professional environment, information and communication in the structure of professional organizations, professional self-actualization. The results of the analysis of risks to teacher’s professional health allowed to identify such groups of risks to teacher’s professional health as “destructive communication”, “destabilizing organization of professional activities”, “destructions of professional self-affirmation” and “demotivators of work productivity”. The content, characteristics and consequences of the negative impact of the components in each of the identified risk groups on teacher’s professional health have been defined. It is shown that there is a negative correlation between risk groups of “destructive communication» and «destabilizing organization of professional activities”.
Keywords: professional health, professional health risks, destructive communication, destabilizing organization of professional activities, destruction of professional self-affirmation, demotivators of work productivity